Rational Unified Proses Dalam Pembagunan Web Aplikasi Administratif Rukun Tetangga (RT) - Dony Oscar (FORMAT, 2020)
According to Regulation of the Minister of Home Affairs Number 5 of 2007 concerning Guidelines for Structuring of Civil Society Organizations, that RT / RW has the functions of: (a) Population and other administrative administration services data, (b) Maintenance of security, order and harmony of life between citizens; (c) Making ideas in the implementation of development by developing the aspirations and pure self-help of the community; and (d) self-help cooperatives and community participation in the region (Septiani, 2018). This RT 4 stewardship has been formed and is located in Rihan Jihan Akbar housing complex with one of its aims to provide administrative services that are needed by residents of Rihan Jihan Akbar housing. In the management of this RT, the main activity is the monthly contribution of residents who will be allocated for infrastructure development within the RT itself and various letters needed to support the management needs of the RT itself such as managing domicile, death and cover letters from the RT itself. To support the management activities of the residents themselves. And can make it easier for citizens to access the needs needed in daily life, we need a system that is more effective and efficient both for administrators to help citizens who need letters or other administrative services. Rational unified process is a system development process covering the entire software development lifecycle that provides an approach to assist the tasks and responsibilities of an organizational development, RUP was created, developed and managed by Rational Software now IBM. The aim is to produce high-quality software that meets user needs(Supriadi & Hardian, 2019).